2020
DOI: 10.1007/s40618-020-01386-3
|View full text |Cite
|
Sign up to set email alerts
|

What factors have impact on glucocorticoid replacement in adrenal insufficiency: a real-life study

Abstract: Purpose The impact of patient's characteristics on glucocorticoid (GC) replacement therapy in adrenal insufficiency (AI) is poorly evaluated. Aims of this study were to assess the influence of sex and body weight on GC dosing and to describe the choice of GC in AI of different etiologies. Methods We retrospectively evaluated hydrocortisone (HC) equivalent total daily dose (HC-TDD) and per-kg-daily dose (HC-KDD) in 203 patients (104 primary AI [pAI], 99 secondary AI [sAI]) followed up for ≥ 12 months. They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
2
2
0
Order By: Relevance
“…Before our study, the previously longitudinal assessment of FC treatment in PAI described a median time between assessments of 433 days (without an intermediate visit, and the longer follow-up lasted less than 6 years) [ 20 ]. Our observation period, close to a study recently reported in patients with adrenal insufficiency [ 28 ], is sufficient to propose a modification in the replacement treatment and consistent to observe a measurable clinical-endocrine difference. A long-term follow-up is of utmost importance because the modification of a lifelong treatment, to personalize replacement therapy, requires several attempts and a close doctor-patient relationship to increase treatment adherence and reduce therapeutic inertia [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Before our study, the previously longitudinal assessment of FC treatment in PAI described a median time between assessments of 433 days (without an intermediate visit, and the longer follow-up lasted less than 6 years) [ 20 ]. Our observation period, close to a study recently reported in patients with adrenal insufficiency [ 28 ], is sufficient to propose a modification in the replacement treatment and consistent to observe a measurable clinical-endocrine difference. A long-term follow-up is of utmost importance because the modification of a lifelong treatment, to personalize replacement therapy, requires several attempts and a close doctor-patient relationship to increase treatment adherence and reduce therapeutic inertia [ 29 ].…”
Section: Discussionsupporting
confidence: 87%
“…Before our study, the previously longitudinal assessment of FC treatment in PAI described a median time between assessments of 433 days (without an intermediate visit, and the longer follow-up lasted less than 6 years) [20]. Our observation period, close to a study recently reported in patients with adrenal insufficiency [28], is sufficient to propose a modification in the replacement treatment and consistent to observe a measurable clinical-endocrine difference.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations